Epidemiology of ambulance utilized patients in Addis Ababa, Ethiopia - Menbeu Sultan; Yonas Abebe; Assefu Welde Tsadik; Catherine Ann Jennings; Nee-Kofi (BMC, 2018)
Abstract Background Well organized and appropriately utilized pre-hospital emergency services play a critical role in augmenting emergency care systems. The primary objective of this study was to understand the demographic and clinical profile of patients who used ambulances in Addis Ababa. The secondary objectives were to assess ambulance response time, transport time and reasons for referral amongst inter-facility transported patients in Addis Ababa. Methods The study was designed as a cross-sectional retrospective chart review of ambulance transported patients using ambulance station records from Addis Ababa Fire and Emergency Prevention and Control Authority. With IRB approval, simple random sampling and manual review of six months of clinical records was performed. Data were collected by trained data collectors and descriptive analysis was done using SPSS version 20. Results Female patients used ambulance services more often than males (female to male ratio of 3:1) and the mean age of the patients was 26 years. The most commonly transported age group was 16-30 years, followed by 31-50 years and neonatal patients (i.e. < 1 month). The majority of the patients had pregnancy related illnesses (n = 492, 61.4%), followed by general medical issues (n = 210, 26.2%) and injury secondary to trauma (n = 99, 12.3%). Most patients (n = 702, 87.6%) were transported for inter-facility transfers, while only 12.4% (n = 99) were primary responses (i.e. from the scene). Prolonged labor was the most common reason (n = 103, 23.4%) for inter-facility transfer of pregnant patients, followed by premature rupture of the amniotic membrane (n = 60, 13.6%). The mean dispatch to scene time interval was 10.1 min, and mean scene to facility time interval was 17.2 min. Conclusion Inter-facility transfers accounted for the largest proportion of ambulance utilization and dispatch in Addis Ababa. Ambulance transport time was twice as long compared to international recommendations of less than eight minutes for emergent transports. The most common reasons for ambulance dispatch were Obstetric. We recommend urgent action to decrease the transport times and to dedicate further pre-hospital resources to address the high burden of inter-facility transfers.